G179(P) EastMidlands Paediatric HIV Network. (27th April 2016) - Bandi, S; Cliffe, L; Balasubramaniam, V; Thompson, F
Abstract : Background: The East Midlands Paediatric HIV network was established in 2011 with the aim of strengthening and improving service provision through a Networked Model of Care. Service Model: Services are provided in the East Midlands both in Tertiary Centres and District General Hospitals with links to specialist centres based in London. The Children's HIV Network (CHINN) and Paediatric HIV Service Specification recommend a formal hub and spoke Network for each region. It was decided that the Hub centre would provide medical and specialist nursing support to the local hospitals within the East Midlands. Provision: The network received financial assurance for the specialist services at the hub centre and research services at Nottingham in addition to the specialist nursing provision at Nottingham, Derby and Northampton. The support covers the following: Consultant time for: Direct patient care/ transition clinics in each area according to number and service needs. Local and national audit and research for the East MidlandsService development and teaching 1.5 wte Paediatric HIV specialist nurses to work flexibly across the East Midlands:0.75 wte Northampton General Hospital NHS Trust (Base)0.75 wte Nottingham University Hospital NHS Trust (Base) 0.75 WTE HIV Paediatric Specialist Nurse Measurable Outcomes: A Dashboard was created to collect data and provide quality assurance to the commissioners (see Table 1 ). The hub centre collates data from other centres and reports on the measurable outcomes on an annual basis. Professionals from all the centres meet annually as part of the Midlands CHIVA meetings. Conclusion: The East Midlands Paediatric HIV Network has been running successfully since 2011 and is a good example of an efficient Networked Model of Care. The dashboard is the only existing one of its kind nationally in Paediatric HIV care. It demonstrates year on year improvement in some important aspects of care, particularly on vaccine uptake and early disclosure of HIV status to the young children. As services are rationalised and Networked Models evolve in many areas of Specialised Services, the East Midlands Network has been hailed as being 'ahead of the game'.